Die weltbildgesteuerte kulturelle Zeit- und Raumkonstruktion Eine empirische Untersuchung an polnischem Material - Fleischer, Michael (Specimina philologiae Slavicae, 1996)
The work presents the results of a survey on the hypothesis - the culture-conditioned and world-driven time and space construction on the basis of time and space words, a survey, with the help of which the expression of this construction has been determined in a single culture.